2020
DOI: 10.1001/jamasurg.2019.5047
|View full text |Cite
|
Sign up to set email alerts
|

Association of Treatment Inequity and Ancestry With Pancreatic Ductal Adenocarcinoma Survival

Abstract: IMPORTANCE Pancreatic ductal adenocarcinoma (PDAC) has a higher incidence and worse outcomes among black patients than white patients, potentially owing to a combination of socioeconomic, biological, and treatment differences. The role that these differences play remains unknown.OBJECTIVES To determine the level of survival disparity between black and white patients in a modern PDAC cohort and whether treatment inequity is associated with such a disparity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 28 publications
6
50
1
Order By: Relevance
“…When we explore the risk factor for survival rate, black people have a shorter survival time compared with other race, and the results have been demonstrated in many cancers [28][29][30], but the study found the black people have a better survival outcome when controlling for stage at the time of treatment [29]. Marital status has no difference in patient prognosis for pancreatic tumor, but some studies have reported the variable was a critical factor that could directly affect the clinical prognosis in other cancers [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…When we explore the risk factor for survival rate, black people have a shorter survival time compared with other race, and the results have been demonstrated in many cancers [28][29][30], but the study found the black people have a better survival outcome when controlling for stage at the time of treatment [29]. Marital status has no difference in patient prognosis for pancreatic tumor, but some studies have reported the variable was a critical factor that could directly affect the clinical prognosis in other cancers [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…14 While pancreatic cancer affects all populations in the United States, certain groups may bear a disproportionate burden of delayed cancer care compared with other groups. [15][16][17][18] For example, a larger proportion of minorities have traditionally presented with later-stage disease and, in turn, lower utilization of curative-intent therapy, and worse long-term outcomes. 19 Despite timeliness of care (i.e., the rapid initiation of treatment after definitive diagnosis) being a key component of high-quality cancer treatment, data on the topic have been somewhat scarce.…”
Section: Introductionmentioning
confidence: 99%
“…While pancreatic cancer affects all populations in the United States, certain groups may bear a disproportionate burden of delayed cancer care compared with other groups 15–18 . For example, a larger proportion of minorities have traditionally presented with later‐stage disease and, in turn, lower utilization of curative‐intent therapy, and worse long‐term outcomes 19 …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated the underlying etiologies of racial disparities in pancreatic cancer survival. It has been proposed that socioeconomic factors such as health insurance status, access to high‐volume cancer centers, referral to multi‐disciplinary cancer care, and refusal of indicated treatment may contribute to worse long‐term outcomes among Black patients 14,39,40,44,44,45 . In a recent study of over 280,000 patients with resected pancreatic cancer identified within the NCDB, Black race was associated with overall worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also demonstrated that Black patients with pancreatic cancer are less likely to undergo surgical resection regardless of cancer stage, especially when presenting to low‐volume, non‐National Cancer Institute/National Comprehensive Cancer Network‐designated cancer care hospitals. In addition, Black patients are less likely to receive perioperative multimodality therapy 8–20 …”
Section: Introductionmentioning
confidence: 99%